Cannabinoids and the Immune System. (1st June 2001) - Klein, Thomas W; Newton, Catherine A; Friedman, Herman
Abstract : The effect of cannabimimetic agents on the function of immune cells such as T and B lymphocytes, natural killer cells and macrophages has been extensively studied over the past several decades using human and animal paradigms involving whole animal models as well as tissue culture systems. From this work, it can be concluded that these drugs have subtle yet complex effects on immune cell function and that some of the drug activity is mediated by cannabinoid receptors expressed on the various immune cell subtypes. However, the overall role of the cannabinoid system of receptors and ligands in human health and disease is still unclear and requires extensive elucidation. Further studies will define the precise structure and function of the putative immunocannabinoid system, the potential therapeutic usefulness of these drugs in chronic diseases such as acquired immune deficiency syndrome and multiple sclerosis, the effects of these agents on tumour growth and induction of apoptosis, and the potential anti-inflammatory and proinflammatory properties of cannabimimetic compounds. It is likely that the cannabinoid system, along with other neuroimmune systems, has a subtle but significant role in the regulation of immunity and that this role can eventually be exploited in the management of human disease.